Idea zrównoważonego rozwoju jako zasada sprawiedliwości - Płachciak, Adam (Annales. Etyka w Życiu Gospodarczym, 2009)
The subject of the paper is an attempt of investigation the idea of sustainable development as an instantiation the principle of justice. Occurring global threads at the and of twenty century as consequences of rapid waste of natural resources, growth of impurity of environment, increase of human population, unsatisfied basic needs of people and global destabilization of natural and socio-economical systems made different environments seek for rational solutions of those problems. Finally as a result of notified by international comities propositions the idea of sustainable development came into existence. Great impact on arising the idea of sustainable development came from so called Brundtland Rapport in 1987. In the document it was stated that one of the conditions of sustaining development in the World requires such development which would satisfy needs of present gen-erations without depriving future generations abilities and satisfactions of their needs. In reference to the idea of sustainable development two-fold purposes were undertaken: (1) instantiation of distributive justice criteria, and (2) explaining validity of future generation justice.